1992
DOI: 10.1128/aem.58.4.1276-1283.1992
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Pseudomonas pickettii strains that degrade 2,4,6-trichlorophenol and their dechlorination of chlorophenols

Abstract: Three strains of Pseudomonas pickettii that can grow with 2,4,6-trichlorophenol (2,4,6-TCP) as the sole source of carbon and energy were isolated from different mixed cultures of soil bacterial populations that had been acclimatized to 2,4,6-TCP. These strains released 3 mol of chloride ion from 1 mol of 2,4,6-TCP during the complete degradation of the TCP. Of these strains, P. pickettii DTP0602 in high-cell-density suspension cultures dechlorinated various chlorophenols (CPs). Cells that were preincubated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 26 publications
1
46
1
Order By: Relevance
“…At present, we do not know the catabolic pathways of degradation of trichlorophenols by A. eutrophus. The formation of 2,6-dichlorohydroxyquinone and 2,6-dichloro-p-benzoquinone have been reported in other bacteria [20,21]. Under our experimental conditions, we were unable to detect such intermediates.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…At present, we do not know the catabolic pathways of degradation of trichlorophenols by A. eutrophus. The formation of 2,6-dichlorohydroxyquinone and 2,6-dichloro-p-benzoquinone have been reported in other bacteria [20,21]. Under our experimental conditions, we were unable to detect such intermediates.…”
Section: Discussioncontrasting
confidence: 50%
“…strain GPl was found to grow only on 2,4,6-trichlorophe-no1 and degrade a few other chlorophenols [20]. On the other hand, Pseudomonas pickettii DTPO602 grows well on 2,4,6-trichlorophenol and their resting cells partially degrade 2,4,5-trichlorophenol [21]. These two strains, along with A. eutrophus JMP134, use a narrow range of chlorophenols as carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…The soil microbial community harbors numerous bacteria with different sensitivities. However, the sensititvity for chlorophenols was found to be not significantly different between chlorophenol-degrading strains and chlorophenol nondegrading strains [22]. Furthermore, we do not expect that the effect of pH on the relative toxicity of chlorophenols for strain P5 is unique because the target of toxic action is the phospholipid membrane.…”
Section: Discussionmentioning
confidence: 94%
“…The mechanisms for the aerobic degradation of chlorinated phenols containing more than three chlorine substituents differ from that of monoand dichlorophenols. Several aerobic bacteria, belonging to the genera Rhodoeoccus, Mycobacterium, Arthrobacter, Flavobacterium, Pseu- 33 domonas and Azotobacter, that degrade pentachlorophenol and/or other polychlorinated phenols have been isolated [36][37][38][39][40][41][42][43][44][45]. In several of the studies, mineralization of pentachlorophenol was demonstrated by using a =4C-labelled substrate or by measuring stoichiometric release of chloride.…”
Section: Aerobic Bacterial Degradation Of Halophenolsmentioning
confidence: 99%
“…In these strains the initial para-hydroxylase was mem- CG-2 also degraded pentabromo-and pentafluorophenol through an identical pathway [403]. Chlorinated para-hydroquinones have also been found as intermediates in polychlorophenol degradation by several other bacteria [38,44,45,51,57,58]. A pentachlorophenol-degrading coryneform bacterium Arthrobacter sp.…”
Section: Aerobic Bacterial Degradation Of Halophenolsmentioning
confidence: 99%